(untitled) (Polish Yearbook of International Law, 2021)
Book review of Aleksander Orakhelashvili, International Law and International Politics: Foundations of Interdisciplinary Analysis, Edward Elgar Publishing, Cheltenham: 2020, pp. 320 (ISBN 978-1-83910-643-9).